2016
DOI: 10.1061/(asce)hy.1943-7900.0001080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relative Column Width and Pile-Cap Elevation on Local Scour Depth around Complex Piers

Abstract: An experimental campaign of 25 long-duration (13-47 days) laboratory tests was carried out with three complex pier models under steady clear-water flow conditions. Each model, characterized by a different relation between the column and the pile-cap widths, D c =D pc , was tested for a variety of pile-cap positions relatively to the initial bed, H c. The experimental data were used to describe the temporal evolution of the scour depth as a function of H c =h (h = approach flow depth). The common criterion to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The flow depth y 0 was fixed at 0.15 m. The pile-cap elevation was fixed at H c = 0.06 m and the base of the pile-cap was at the original bed level. This position is typical and leads to enlarged scour hole, as previous studies (Ataie-Ashtiani et al [18], Moreno et al [22], and Yang et al [28]) have shown that the scour depth is maximized when the pile-cap is near the original bed level. For each pier arrangement, a wide range of flow intensity ratios (U/U c ) were tested, from 0.9 to 4.0-5.2, to investigate scour features under both clear-water (U/U c ≤ 1) and live-bed (U/U c > 1) flow regimes.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…The flow depth y 0 was fixed at 0.15 m. The pile-cap elevation was fixed at H c = 0.06 m and the base of the pile-cap was at the original bed level. This position is typical and leads to enlarged scour hole, as previous studies (Ataie-Ashtiani et al [18], Moreno et al [22], and Yang et al [28]) have shown that the scour depth is maximized when the pile-cap is near the original bed level. For each pier arrangement, a wide range of flow intensity ratios (U/U c ) were tested, from 0.9 to 4.0-5.2, to investigate scour features under both clear-water (U/U c ≤ 1) and live-bed (U/U c > 1) flow regimes.…”
Section: Methodsmentioning
confidence: 62%
“…In addition, the existence of the weir leads to upstream bed aggradation and consequently changes the relative pile-cap elevation to the original bed level. The relative pile-cap elevation has been considered as a key factor affecting the scour development and equilibrium scour depth at complex piers (Coleman [16]; Ataie-Ashtiani et al [18]; Moreno et al [22]; Yang et al [28]). Similar effects can also be caused by general bed degradation that usually occurs downstream of sluice gates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also introduced the concept of non-dimensionalising scour using an equivalent diameter length scale which is calculated using an empirical relationship. Moreno et al (2015) recently examined the effect that different structural parameters of cylindrical based structures have on the temporal evolution of scour and concluded that the rate of scour is associated with the progressive physical presence in the scour hole evolution of one, two, or three structural components of the non-uniform cylindrical pier.…”
Section: Introductionmentioning
confidence: 99%
“…,Lança et al (2013),Moreno et al (2014),Moreno et al (2016), andMoreno et al (2017). For t ≥ 3 day, additional data sources were:Sheppard (2003),Beheshti et al (2013),Chreties et al (2013), andKeshavarzi et al (2018).…”
mentioning
confidence: 99%